If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -3)(x + 5) + -2(x + -2) = 2(x + 3) * 2 + -1 Reorder the terms: (-3 + 2x)(x + 5) + -2(x + -2) = 2(x + 3) * 2 + -1 Reorder the terms: (-3 + 2x)(5 + x) + -2(x + -2) = 2(x + 3) * 2 + -1 Multiply (-3 + 2x) * (5 + x) (-3(5 + x) + 2x * (5 + x)) + -2(x + -2) = 2(x + 3) * 2 + -1 ((5 * -3 + x * -3) + 2x * (5 + x)) + -2(x + -2) = 2(x + 3) * 2 + -1 ((-15 + -3x) + 2x * (5 + x)) + -2(x + -2) = 2(x + 3) * 2 + -1 (-15 + -3x + (5 * 2x + x * 2x)) + -2(x + -2) = 2(x + 3) * 2 + -1 (-15 + -3x + (10x + 2x2)) + -2(x + -2) = 2(x + 3) * 2 + -1 Combine like terms: -3x + 10x = 7x (-15 + 7x + 2x2) + -2(x + -2) = 2(x + 3) * 2 + -1 Reorder the terms: -15 + 7x + 2x2 + -2(-2 + x) = 2(x + 3) * 2 + -1 -15 + 7x + 2x2 + (-2 * -2 + x * -2) = 2(x + 3) * 2 + -1 -15 + 7x + 2x2 + (4 + -2x) = 2(x + 3) * 2 + -1 Reorder the terms: -15 + 4 + 7x + -2x + 2x2 = 2(x + 3) * 2 + -1 Combine like terms: -15 + 4 = -11 -11 + 7x + -2x + 2x2 = 2(x + 3) * 2 + -1 Combine like terms: 7x + -2x = 5x -11 + 5x + 2x2 = 2(x + 3) * 2 + -1 Reorder the terms: -11 + 5x + 2x2 = 2(3 + x) * 2 + -1 Reorder the terms for easier multiplication: -11 + 5x + 2x2 = 2 * 2(3 + x) + -1 Multiply 2 * 2 -11 + 5x + 2x2 = 4(3 + x) + -1 -11 + 5x + 2x2 = (3 * 4 + x * 4) + -1 -11 + 5x + 2x2 = (12 + 4x) + -1 Reorder the terms: -11 + 5x + 2x2 = 12 + -1 + 4x Combine like terms: 12 + -1 = 11 -11 + 5x + 2x2 = 11 + 4x Solving -11 + 5x + 2x2 = 11 + 4x Solving for variable 'x'. Reorder the terms: -11 + -11 + 5x + -4x + 2x2 = 11 + 4x + -11 + -4x Combine like terms: -11 + -11 = -22 -22 + 5x + -4x + 2x2 = 11 + 4x + -11 + -4x Combine like terms: 5x + -4x = 1x -22 + 1x + 2x2 = 11 + 4x + -11 + -4x Reorder the terms: -22 + 1x + 2x2 = 11 + -11 + 4x + -4x Combine like terms: 11 + -11 = 0 -22 + 1x + 2x2 = 0 + 4x + -4x -22 + 1x + 2x2 = 4x + -4x Combine like terms: 4x + -4x = 0 -22 + 1x + 2x2 = 0 Begin completing the square. Divide all terms by 2 the coefficient of the squared term: Divide each side by '2'. -11 + 0.5x + x2 = 0 Move the constant term to the right: Add '11' to each side of the equation. -11 + 0.5x + 11 + x2 = 0 + 11 Reorder the terms: -11 + 11 + 0.5x + x2 = 0 + 11 Combine like terms: -11 + 11 = 0 0 + 0.5x + x2 = 0 + 11 0.5x + x2 = 0 + 11 Combine like terms: 0 + 11 = 11 0.5x + x2 = 11 The x term is 0.5x. Take half its coefficient (0.25). Square it (0.0625) and add it to both sides. Add '0.0625' to each side of the equation. 0.5x + 0.0625 + x2 = 11 + 0.0625 Reorder the terms: 0.0625 + 0.5x + x2 = 11 + 0.0625 Combine like terms: 11 + 0.0625 = 11.0625 0.0625 + 0.5x + x2 = 11.0625 Factor a perfect square on the left side: (x + 0.25)(x + 0.25) = 11.0625 Calculate the square root of the right side: 3.326033674 Break this problem into two subproblems by setting (x + 0.25) equal to 3.326033674 and -3.326033674.Subproblem 1
x + 0.25 = 3.326033674 Simplifying x + 0.25 = 3.326033674 Reorder the terms: 0.25 + x = 3.326033674 Solving 0.25 + x = 3.326033674 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.25' to each side of the equation. 0.25 + -0.25 + x = 3.326033674 + -0.25 Combine like terms: 0.25 + -0.25 = 0.00 0.00 + x = 3.326033674 + -0.25 x = 3.326033674 + -0.25 Combine like terms: 3.326033674 + -0.25 = 3.076033674 x = 3.076033674 Simplifying x = 3.076033674Subproblem 2
x + 0.25 = -3.326033674 Simplifying x + 0.25 = -3.326033674 Reorder the terms: 0.25 + x = -3.326033674 Solving 0.25 + x = -3.326033674 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.25' to each side of the equation. 0.25 + -0.25 + x = -3.326033674 + -0.25 Combine like terms: 0.25 + -0.25 = 0.00 0.00 + x = -3.326033674 + -0.25 x = -3.326033674 + -0.25 Combine like terms: -3.326033674 + -0.25 = -3.576033674 x = -3.576033674 Simplifying x = -3.576033674Solution
The solution to the problem is based on the solutions from the subproblems. x = {3.076033674, -3.576033674}
| 4y+5=22 | | 10x-0.2=7x+0.1 | | 4+2+7v-5=1+6v | | 6x-10=2x+2(2x-5) | | 3+4(x-1)=7(x+1)-x | | 6x+5=-2(5-3x) | | 2x-7=2(x+9) | | 3x+6=-2x+7+5x | | 2*5-5y=-10 | | -8(n+7)=-24+8n | | 0.4(2z+7)+18.4=0.7(2z-4) | | 2(x+6)-4=6(x-1)-2x | | -8r+2=2(r+6) | | x^2+36=3x | | 22x+11=25x-4 | | -100=b*(-72) | | -2x+9=x-12 | | 0.35x+0.85(10-x)=4 | | x+7-(x-8)=2x+1 | | 49x^2-91x+42=0 | | y+23=0 | | 2x+y=6.75 | | 9+5x=2x | | 5s-2+3y(s-11)=5 | | N+P+V+A+A+P+C+I=POS | | 5x-3=-3-x | | (8x-3)(-10x+3)=(8x-3)(3) | | 2-3x+x=14 | | 5x-(2x-6)=21 | | 5m-8=3m | | 7g-4g=17-8 | | x*x=3x+20 |